Burnout in the NICU setting and its relation to safety culture. Issue 10 (17th April 2014) - Profit, Jochen; Sharek, Paul J; Amspoker, Amber B; Kowalkowski, Mark A; Nisbet, Courtney C; Thomas, Eric J; Chadwick, Whitney A; Sexton, J Bryan
Abstract : Background: Burnout is widespread among healthcare providers and is associated with adverse safety behaviours, operational and clinical outcomes. Little is known with regard to the explanatory links between burnout and these adverse outcomes. Objectives: (1) Test the psychometric properties of a brief four-item burnout scale, (2) Provide neonatal intensive care unit (NICU) burnout and resilience benchmarking data across different units and caregiver types, (3) Examine the relationships between caregiver burnout and patient safety culture. Research design: Cross-sectional survey study. Subjects: Nurses, nurse practitioners, respiratory care providers and physicians in 44 NICUs. Measures: Caregiver assessments of burnout and safety culture. Results: Of 3294 administered surveys, 2073 were returned for an overall response rate of 62.9%. The percentage of respondents in each NICU reporting burnout ranged from 7.5% to 54.4% (mean=25.9%, SD=10.8). The four-item burnout scale was reliable (α=0.85) and appropriate for aggregation (intra-class correlation coefficient-2=0.95). Burnout varied significantly between NICUs, p<0.0001, but was less prevalent in physicians (mean=15.1%, SD=19.6) compared with non-physicians (mean=26.9%, SD=11.4, p=0.0004). NICUs with more burnout had lower teamwork climate (r=−0.48, p=0.001), safety climate (r=−0.40, p=0.01), job satisfaction (r=−0.64, p<0.0001), perceptions of management (r=−0.50, p=0.0006) and working conditions (r=−0.45, p=0.002). Conclusions: NICU caregiver burnout appears to have 'climate-like' features, is prevalent, and associated with lower perceptions of patient safety culture.